3a+9=2a-1

Simple and best practice solution for 3a+9=2a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a+9=2a-1 equation:



3a+9=2a-1
We move all terms to the left:
3a+9-(2a-1)=0
We get rid of parentheses
3a-2a+1+9=0
We add all the numbers together, and all the variables
a+10=0
We move all terms containing a to the left, all other terms to the right
a=-10

See similar equations:

| (8,-8)m=1/8 | | 0.2(5x−6)+2x=0.8 | | 1/2t=4=3 | | -16-8n=-10 | | -4f=-48 | | 4b-(7)=37 | | x/9-5=17/18 | | (2x^2+7x-49)=0 | | 2-x=-2x-8 | | 11-2(8+3x)=14 | | 40(14.50)=26n+8 | | 2/3h-156=3^13/24 | | 5(7x)+4+2=30 | | 3(2x-2)=(2x+3) | | (22^2+7x-49)=0 | | -22=-2(5+k) | | 14=7x-30 | | 40z^2+43z=0 | | 3d-9=5d-11 | | 11/6r-1=5/6r | | 2(a-6)^2-45=53 | | 3d-9=5d-11. | | y/12+5=-19 | | 8(3-x)=2x+5 | | x•11=73 | | -9x-4=-11 | | -4x=29-5 | | 12/32=x/20 | | 12+3x=0.5x-8 | | 2x(x+1)-2=2(x-2)(x+3) | | -42-11x+15x=94 | | 2(p-10)=14 |

Equations solver categories